It Framework Design Parameters - Laxton, Douglas; Freedman, Charles (Washington, D.C. : International Monetary Fund, 2009)
This is the third chapter of a forthcoming monograph entitled "On Implementing Full-Fledged Inflation-Targeting Regimes: Saying What You Do and Doing What You Say." It examines a number of elements in the design of an inflation-targeting framework. These include the definition of the target variable, the relevance of core measures of inflation, and the advantages and disadvantages of point targets, point targets with a band, and range targets. It then discusses the choice of a long-term inflation rate, the target horizon, and the policy horizon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet